Abusive leadership and employee commitment nexus: Conservation of resources theory perspective - Usama Bin Jabbar; Farida Saleem; Muhammad Imran Malik; Saiqa Saddiqa Qureshi; Ramayah Thursamy (Cogent Business & Management, 2020)
Leadership styles have direct impact on employee commitment and may influence organizational sustainability. Previously the positive aspects of leadership are highlighted, and negative aspects still need to bring to light. This study aims to examine the relationship of abusive leadership and organizational commitment of bank employees where in employee's emotional intelligence acts as a mediator. A sample of 255 bank employees was selected and their responses were gathered through closed-ended questionnaires. PLS-SEM was used for analysis by using SmartPLS Ver. 3.0. The results show that the abusive behaviors disrupt organizational commitment of bank employees. Despite the fact that emotional intelligence mediates the relationship but could not turn organizational commitment to positive due to strong negative intensity of abusive leadership. This study therefore recommends that employee commitment is likely to be achieved when the negative effects of abusive leadership can be weakened through using emotional intelligence by the bank employees. The paper selected a sample from banking sector from a developing country and tested a model empirically. The findings are novel to highlight the presence of abusive/toxic leadership in the banks.
Keywords: 650; abusive leadership; banks; emotional intelligence; organizational commitment; Pakistan